Crack coalescence and strain accommodation in gypsum rock (Fracture and Structural Integrity, 2020)
Gypsum is a soft rock with low strength and high propensity to plastic deformation. Its mechanical properties are relevant in a wide range of technical application (e.g. tunnel excavation, stability assessment of underground quarries, oil and gas accumulation). The micro-mechanisms involved in the deformation of gypsum rock have for long time interested the scientific world and are still not completely understood. The peculiar crystallographic structure of this bi-hydrate salt, with water molecules layered in the salt structure, favours the development of plastic structures in the rock. The present work proposes an experimental investigation of strain accommodation mechanisms in gypsum rock, reporting data referred to uniaxial and triaxial stress conditions. The rock strain was studied with a multiscale approach, with the comparison of results from DIC and microstructural analyses.
Keywords: Gypsum; DIC analysis; Microstructure; Brittle-ductile transition